E→E+T | E-T | T T→T* F | T/F | F F→P^ F | P P→(E) | i
E→E1+T1 {E.place:=newtemp; emit(E.place , ":=" ,E1.place,‘+‘ , T1.place)} (+, E1.val ,T1.val,E.val) E→E1-T1 {E.place:=newtemp; emit(E.place , ":=" ,E1.place,‘-‘ , T1.place)} (-, E1.val ,T1.val,E.val) E→T1 {E.place:=T1.place;} T→T1* F1 {T.place:=newtemp; emit(T.place , ":=" ,T1.place,‘*‘ , F1.place)} (*, T1.val ,F1.val,T.val) T→T1/F1 {T.place:=newtemp; emit(T.place , ":=" , T1.place,‘/‘ , F1.place)} (/, T1.val ,F1.val,T.val) T→F1 {T.place:=F1.place;} F→P1^F1 {T.place:=newtemp; emit(F.place , ":=" , P1.place,‘^‘ , F1.place)}(^, P1.val ,F1.val,F.val) F→P1 {F.place:=newtemp; emit(F.place , ":=" , P1.place)} P→(E1) {P.place:=E1.place} P→i {P:=lookup(id.name); if P<>nil then P.place:=i else error}
2.(选做)实验三:语法制导的语义翻译程序
要求:
如
输入:a+b*c,则输出
(*,b,c,T1)
(+,a,T1,T2)
输入:b*(c+b)*d,则输出
(*,b,c,T1)
(*,b,d,T2)
(+,T1,T2,T3)
原文:https://www.cnblogs.com/Rakers1024/p/12071817.html